Metal and nylon heterogeneous connection material with high interface bonding strength and preparation method of metal and nylon heterogeneous connection material

By chemical etching on the metal surface and coating low-melting point nylon resin, combined with ultrasonic assisted injection molding technology, the problem of insufficient interface bonding strength between metal and resin-based composite materials is solved, and the mechanical properties of the material are significantly improved.

CN119704528AActive Publication Date: 2025-03-28NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411971049.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the interface bonding strength between metal and resin-based composite materials, resulting in insufficient mechanical properties of the hybrid structure of metal and resin-based composite materials.

Method used

Micron-scale porous structure is constructed on the metal surface by chemical etching, and the metal surface is coated with low-melting point nylon resin, combined with ultrasonic assisted injection molding technology, enhance the interface bond strength between metal and nylon resin-based composite materials.

Benefits of technology

It significantly improves the interface bonding strength between metal and nylon resin-based composite materials, enhances the mechanical properties of the materials, and is suitable for automobiles, ships, rail transit and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704528A_ABST
    Figure CN119704528A_ABST
Patent Text Reader

Abstract

The invention discloses a metal and nylon heterogeneous connection material with strong interface bonding strength and a preparation method thereof, and the preparation method comprises the following steps: cleaning a metal sample to remove oil stain on the surface, and carrying out chemical etching treatment to obtain metal with porous and hydroxyl groups on the surface; coating a nylon solution, drying to remove a solvent, and annealing to obtain metal of which the surface is coated with nylon; and carrying out ultrasonic-assisted injection molding with injection molding nylon resin to obtain the heterogeneous connection material. A micron-sized porous structure is constructed on the metal surface by a chemical etching method, the metal surface is coated with low-melting-point nylon resin, and high-temperature tempering treatment is performed under the protection of inert gas, so that the nylon resin can better permeate into the porous structure on the metal surface, and the surface of the metal is more uniform. Better compatibility of the metal and the injection molding grade nylon resin matrix is promoted, so that the interface bonding strength between the metal and the nylon resin matrix composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heterogeneous material of metal and resin or a composite material thereof, and in particular to a metal and nylon heterogeneous connection material with strong interface bonding strength and a preparation method thereof. Background Art

[0002] The hybrid structure of metal and thermoplastic resin-based composites has broad prospects in the fields of automobiles, ships, rail transit, etc. The hybrid structure of metal and resin-based composites not only has the high strength and high compressive resistance of metals, but also has the advantages of chemical corrosion resistance and fatigue resistance of thermoplastic composites, and greatly reduces the weight of the product. Due to the large difference in physical and chemical properties between resin-based composites and metals, achieving efficient and reliable connection between the two is one of the technical problems that need to be solved urgently.

[0003] Improving the interfacial bonding strength between metal and resin-based composite materials is the key to achieving high mechanical properties of metal and resin-based composite hybrid structures. Therefore, when metal and resin-based composite materials are used in combination, the metal surface must be treated to enhance the physical, mechanical and chemical bonding of the interface between the metal and resin-based composite materials. Currently, the commonly used metal surface treatment methods include: anodizing, chemical grafting, laser etching, etc.

[0004] The patent application with publication number CN117698038A discloses a metal-plastic composite and a preparation method thereof, wherein the metal surface is roughened by laser and then placed in an acidic etching solution for corrosion, and then the metal-plastic composite is obtained by injection molding technology. Although this method can improve the interfacial bonding strength between metal and plastic, the melt viscosity of the plastic is relatively high, and it cannot be guaranteed that the plastic melt can fully infiltrate the metal surface. Therefore, the degree of improvement in the interfacial bonding strength between metal and plastic is limited.

[0005] The patent application with the publication number CN118809931A discloses a metal surface treatment method and application based on nano injection molding. After the metal sheet is subjected to electrochemical corrosion treatment to prepare nano-scale holes, raw materials such as terephthalic acid are used to prepare solutions, and the metal sheet is immersed in the solution to generate a PBT-like structure, thereby improving the bonding performance between the metal sheet and the PBT plastic, improving the bonding performance between the resin and the metal sheet, and increasing the bonding strength between the metal and the plastic. Although the solution of raw materials such as terephthalic acid and ethylene glycol can fully infiltrate the metal surface, the molecular weight of the polymer with a PBT-like structure generated by the reaction of terephthalic acid and ethylene glycol at the interface is difficult to control, which will affect the interfacial bonding strength between the PBT resin and the metal.

[0006] Therefore, developing methods to improve the interfacial bonding strength between metal and resin-based composites is of great significance to expanding the application areas of resin-based composites and metal hybrid structures. Summary of the invention

[0007] The present invention aims to solve the problem of weak bonding force between the interface of metal and resin and provides a method for improving the bonding strength of the interface of heterogeneous connection materials of metal and nylon resin-based composite materials. The bonding strength of the interface of metal and nylon resin-based composite materials is improved by combining coating of low-melting-point nylon after chemical etching and ultrasonic-assisted injection molding, thereby providing technical support for the field of metal and nylon resin-based composite material molding technology.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength comprises the steps of:

[0010] Step 1, cleaning the metal sample to remove the oil on the surface, and chemically etching the part connected to the injection-molded nylon resin to obtain a metal with porous and hydroxyl groups on the surface;

[0011] Step 2, coating the metal surface treated in step 1 with a nylon solution, drying to remove the solvent, and then annealing to obtain a metal surface coated with nylon;

[0012] Step 3, subjecting the metal with nylon coating on the surface in step 2 to injection molding nylon resin through ultrasonic assisted injection molding to obtain the metal and nylon heterogeneous connection material.

[0013] In the present invention, a micron-scale porous structure is constructed on the metal surface by chemical etching, and a low-melting-point nylon resin is coated on the metal surface. Under the protection of an inert gas, a high-temperature tempering treatment is performed so that the low-melting-point nylon resin can better penetrate into the porous structure on the metal surface. The surface-coated nylon can promote better compatibility and stronger bonding between the metal and the nylon matrix or the nylon-based composite material, thereby preparing a hybrid product of a metal and resin-based composite material.

[0014] In step 1, the method of removing the surface oil stains includes one or more of inorganic alkali washing, organic solvent washing, aqueous detergent washing, and steam washing;

[0015] The inorganic alkali washing specifically includes: washing the metal with 0.01-10 mol / L sodium hydroxide for 5-60 minutes.

[0016] The chemical etching process in step 1 includes the following steps:

[0017] Step a, immersing the metal of the part connected to the injection-molded nylon resin after degreasing into a hydrochloric acid solution, taking it out, washing and drying it;

[0018] Step b, immersing the acid-treated metal area in an aqueous ammonia solution, taking it out, washing it, and drying it.

[0019] Since aluminum metal is easily oxidized in the air, it is treated with acid. On the one hand, the acid can react with aluminum oxide to form soluble aluminum salts; on the other hand, the acid can also react with aluminum metal to achieve the effect of etching the surface of the material; then alkali is used for treatment. On the one hand, it can neutralize the acid, and on the other hand, it can react with aluminum salts to form aluminum hydroxide. Aluminum hydroxide is an amphoteric hydroxide that can further react with alkali to form tetrahydroxyaluminate ([Al(OH)4] - ), therefore, after the metal aluminum material is treated with acid or alkali, the surface has a certain amount of hydroxyl groups, which improves the hydrophilicity of the material surface and is beneficial to the impregnation performance of the coating resin.

[0020] The concentration of the hydrochloric acid solution is 0.01 to 10 mol / L, and the acid treatment time is 1 to 60 min;

[0021] The concentration of the ammonia solution is 0.5 to 20 mol / L, and the ammonia treatment time is 1 to 60 minutes.

[0022] The melting point of the injection molding nylon resin in step 3 differs from the melting point of the nylon in the nylon solution in step 2 by 20 to 150°C; the purpose of coating the metal surface with nylon is to improve the compatibility of the metal part with the injection molding nylon. During the injection molding in step 3, the coated metal is placed in a mold, and the mold temperature is much lower than the melt temperature of the injection molding resin. After the injection molding resin melt enters the mold, the temperature will decrease. Therefore, the melting point of the nylon used for coating is preferably 20 to 150°C lower than the melting point of the nylon used during injection molding; preferably 50-120°C lower, to ensure that the temperature of the injection molding nylon resin entering the mold is sufficient to quickly melt the resin coating on the metal surface to achieve a fusion connection effect.

[0023] The mass concentration of nylon in the nylon solution is 0.01-20%, and the solvent is one or more of formic acid, trifluoroacetic acid, and phenol. Preferably, the mass concentration of nylon in the nylon solution is 0.1-10%. As the mass concentration of nylon in the nylon solution increases, the interface bonding strength of the heterogeneous connection material between the metal and the nylon resin-based composite material increases, but after reaching a certain concentration, as the mass concentration of nylon in the nylon solution increases, the interface bonding strength decreases. This is because when the solubility of the coating is high, the interface layer formed between the composite material and the metal is thicker, and the thickness of the mutual penetration of the molecular chains of the resin matrix in the composite material and the coated nylon molecular chains is limited, which is lower than the thickness of the interface coating layer. In addition, since the mechanical strength of the coated nylon resin is lower than that of the injection molded nylon, when subjected to a large load, the damage mainly occurs at the interface nylon resin, so the interface bonding strength is reduced instead. It is further preferred that the mass concentration of nylon is 0.01-5%.

[0024] The nylon used in the nylon solution in step 2 includes one or more resins including nylon 6, nylon 66, nylon 1010, high temperature nylon 6T, high temperature nylon 9T, high temperature nylon 10T, high temperature nylon MXD6, and nylon copolymer;

[0025] The metal includes one or more of aluminum, aluminum alloy, copper-aluminum alloy, magnesium-aluminum alloy, and magnesium-titanium alloy.

[0026] The injection molding nylon resin in step 3 includes one or more resins or fiber-reinforced resin composites selected from nylon 6, nylon 66, nylon 1010, high-temperature nylon 6T, high-temperature nylon 9T, high-temperature nylon 10T, high-temperature nylon MXD6, and nylon copolymers; and the fibers include one or more selected from glass fibers, carbon fibers, ceramic fibers, and aramid fibers.

[0027] In step 2, the drying temperature is 60-120° C., and the drying time is 0.2-2 h.

[0028] The ultrasonic power during the injection molding process is 100-1000W, and the ultrasonic time is 3-20s. Ultrasonication during the injection molding process has a very high auxiliary effect on the bonding strength of the interface. The ultrasonic time depends more on the cooling time of the injection molding, but the ultrasonic power has a greater impact. With the increase of ultrasonic power, the viscosity of the resin melt decreases, which improves the impregnation performance and compatibility of the resin on the metal surface, thereby improving the interface bonding strength between the composite material and the metal; but too high power will make the crystallization of the resin imperfect, resulting in a decrease in the interface bonding strength. Preferably, the ultrasonic power during the injection molding process is 100-600W.

[0029] The injection molding process is as follows: barrel temperature 250-380°C, mold temperature 60-200°C, holding pressure 40-160MPa, and cooling time 1-30s.

[0030] The present invention also provides a metal and nylon heterogeneous connection material with strong interface bonding strength obtained by the preparation method. The material can be used in the fields of automobiles, ships, rail transportation, etc.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) In the present invention, after constructing micron-scale pores on the metal surface, a low-melting-point nylon resin is coated, which can not only improve the roughness of the metal surface and promote the mechanical anchoring effect between the metal and the nylon resin matrix, but also enhance the wettability of the metal surface and promote better compatibility between the metal and the injection-molding grade nylon resin matrix, thereby improving the interface bonding strength of the metal and nylon resin-based composite materials.

[0033] (2) The present invention reduces the viscosity of injection-grade nylon resin and improves the fluidity of the matrix through ultrasonic-assisted injection molding, so that the injection-grade nylon resin can further penetrate into the low-melting-point nylon molecules and then penetrate into the pores on the metal surface, thereby enhancing the mechanical anchoring effect and further improving the interface strength between the metal and the nylon resin-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the cross-sectional morphology of the metal and GF / nylon 66 composite material after chemical etching in Comparative Example 2.

[0035] Figure 2 This is a scanning electron microscope image of the cross-sectional morphology of the low-melting-point nylon 66 and GF / nylon 66 composite material coated after chemical etching by ultrasonic-assisted injection molding in Example 2.

[0036] Figure 3 Schematic diagram of a sample with a metal insert during ultrasonic assisted injection molding in an embodiment. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0038] The raw materials used in the following specific embodiments are all purchased from the market. The aluminum alloy plate used in the embodiments of the present invention and the comparative examples is 6061 aluminum-magnesium-silicon aluminum alloy. The nylon resin matrix composite material used in injection molding is GF / nylon 66 composite material from BASF of Germany, with a grade of A3WG5, the melting point of nylon 66 resin is 260℃; coated with nylon 66 resin, the first grade is A3W, melting point is 260℃; the second grade is 8061, melting point is 156℃.

[0039] Interface bonding strength test method (non-standard test method)

[0040] Test method for interfacial bonding strength between metal and resin or its composite materials: On a universal testing machine, the tensile speed is 2mm / min, the test temperature is room temperature 25℃±0.5℃, the load at tensile fracture is measured T (N), and the area of ​​the composite material wrapped around the metal is S (mm 2 ), the calculation formula of the interface bonding strength (F, MPa) between metal and composite materials is F=T / S.

[0041] Comparative Example 1

[0042] Step 1: immerse the metal aluminum insert in a 1.3 mol / L sodium hydroxide solution for 10 minutes to remove oil stains on its surface, then wash it with deionized water until it is neutral, and dry it for later use.

[0043] Step 2: Place the metal insert into the injection mold and inject The GF / nylon 66 composite material of A3WG5 has a mold temperature of 100°C, a barrel temperature of 295°C, a holding pressure of 80MPa, and a cooling time of 10s. According to the interfacial bonding strength test method of metal and resin or composite materials, the interfacial bonding strength test is performed, and the test results are shown in Table 1.

[0044] Comparative Example 2

[0045] Step 1: immerse the metal aluminum insert in a 1.3 mol / L sodium hydroxide solution for 10 minutes to remove oil stains on its surface, then wash it with deionized water until it is neutral, and dry it for later use.

[0046] Step 2: immerse the metal insert with the surface oil removed, and the part connected to the injection-molded nylon composite material in a 1.4 mol / L dilute hydrochloric acid solution for 10 minutes, so that micrometer-level holes are generated on the metal surface, take it out, wash it in deionized water until it is neutral, and dry it for use; immerse the metal etched with the dilute hydrochloric acid solution in ammonia water with a concentration of 14.8 mol / L for 10 minutes, take it out, wash it with deionized water until it is neutral, and dry it;

[0047] Step 3: Place the metal insert obtained after drying into the injection mold and perform injection molding. The GF / nylon 66 composite material of A3WG5 has a mold temperature of 100°C, a barrel temperature of 295°C, a holding pressure of 80MPa, and a cooling time of 10s. According to the test method for the interfacial bonding strength between metal and composite materials, the interfacial bonding strength test was performed, and the test results are shown in Table 1. In addition, the cross-section of the composite material and the metal aluminum is shown in Table 1. Figure 1 As shown in the figure, it can be clearly seen that there are pores at the interface between the composite material and the metal.

[0048] Example 1

[0049] Step 1: immerse the metal aluminum insert in a 1.3 mol / L sodium hydroxide solution for 10 minutes to remove oil stains on its surface, then wash it with deionized water until it is neutral, and dry it for later use.

[0050] Step 2: immerse the metal insert with the surface oil removed, and the part connected to the injection-molded nylon composite material in a 1.4 mol / L dilute hydrochloric acid solution for 10 minutes, so that micrometer-level holes are generated on the metal surface, take it out, wash it in deionized water until it is neutral, and dry it for use; immerse the metal etched by the dilute hydrochloric acid solution in ammonia water with a concentration of 14.8 mol / L for 10 minutes, take it out, wash it with deionized water until it is neutral, and dry it;

[0051] Step 3, select nylon 66 resin with melting points of 156°C and 260°C, respectively, dissolve it in formic acid to prepare a solution of a certain concentration, the concentration is 0.25%, 0.75%, 1%, 5% (specific parameters are shown in Table 1), the solution is coated on the metal surface after chemical etching, placed in a blast oven to remove a large amount of solvent, then placed in a vacuum drying oven to remove the residual solvent, and then placed in a high-temperature furnace under the protection of inert gas to heat to 280°C, keep for 10 minutes, and the metal surface treatment is completed.

[0052] Step 4: Place the surface treated metal insert into the injection mold and perform injection molding. For the GF / nylon 66 composite material of A3WG5, the mold temperature is 100°C, the barrel temperature is 295°C, the holding pressure is 80MPa, and the cooling time is 10s.

[0053] The interface bonding strength of the materials was tested, and the test results are shown in Table 1.

[0054] Example 2

[0055] Step 1: immerse the metal aluminum insert in a 1.3 mol / L sodium hydroxide solution for 10 minutes to remove oil stains on its surface, then wash it with deionized water until it is neutral, and dry it for later use.

[0056] Step 2: immerse the metal insert with the surface oil removed, and the part connected to the injection-molded nylon composite material in a 1.4 mol / L dilute hydrochloric acid solution for 10 minutes, so that micrometer-level holes are generated on the metal surface, take it out, wash it in deionized water until it is neutral, and dry it for use; immerse the metal etched by the dilute hydrochloric acid solution in ammonia water with a concentration of 14.8 mol / L for 10 minutes, take it out, wash it with deionized water until it is neutral, and dry it;

[0057] Step 3, select a formic acid solution of nylon 66 with a melting point of 156°C and a concentration of 0.75% and apply it to the metal surface after chemical etching, place it in a blast oven to remove a large amount of solvent, then place it in a vacuum drying oven to remove the residual solvent, and then place it in a high-temperature furnace under the protection of inert gas to heat it to 280°C and maintain it for 10 minutes, thus completing the metal surface treatment.

[0058] Step 4: Place the surface treated metal insert into the injection mold and perform injection molding. For the GF / nylon 66 composite material of A3WG5, the mold temperature is 100°C, the barrel temperature is 295°C, the holding pressure is 80MPa, the cooling time is 10s, the ultrasonic time is 10S, and the ultrasonic power is 400W.

[0059] Referring to Comparative Example 1, the interface bonding strength test was performed, and the test results are shown in Table 1. In addition, the cross-sectional view of the composite material and the metal aluminum is shown in Table 1. Figure 2 As shown in the figure, it can be clearly seen that there are almost no pores at the interface between the composite material and the metal, and the resin in the composite material is filled into the metal pores. The schematic diagram of the sample with metal inserts is shown in Figure 3 shown.

[0060] Example 3

[0061] The difference from Example 2 is that during the ultrasonic assisted injection molding of the metal and resin-based composite material, the ultrasonic power is 200w, and the conditions of the other steps are the same, and a metal and resin-based composite hybrid product is obtained. Referring to Example 2, the interface bonding strength is tested, and the results are shown in Table 1.

[0062] Comparative Example 3

[0063] The difference from Example 2 is that during the ultrasonic assisted injection molding of the metal and resin-based composite material, the ultrasonic power is 600w, and the conditions of the other steps are the same, and a metal and resin-based composite hybrid product is obtained. Referring to Example 2, the interface bonding strength is tested, and the results are shown in Table 1.

[0064] Table 1 Interface bonding strength between metal and composite materials

[0065]

[0066] As can be seen from Table 1, compared with Example 1, the auxiliary ultrasound in the injection molding process of Example 2 and Example 3 can significantly improve the bonding strength between the resin and the metal. Compared with Comparative Example 3, too high ultrasonic power is not conducive to the result. This is because the ultrasonic power has a greater effect on the viscosity of the resin melt. As the ultrasonic power increases, the viscosity of the resin melt decreases, which improves the impregnation performance and compatibility of the resin on the metal surface, thereby improving the interfacial bonding strength between the composite material and the metal; but too high power will cause the polymer macromolecular chain to break, destroy the crystal structure of the resin, make the crystallization of the resin imperfect, and cause the interfacial bonding strength to decrease.

[0067] The data in Example 1 show that a suitable coating concentration can effectively improve the interfacial bonding strength between metal and composite materials. This is because the use of low-melting nylon 66 resin (Tm = 156 ° C) to coat the metal surface can effectively improve the wettability of the nylon 66 resin matrix in the GF / nylon 66 composite material to the metal surface. Although the temperature of the mold is low, the temperature of the composite material injected into the mold is higher than 156 ° C, which can melt the nylon 66 of the coating layer, so that the molecular chains of the resin matrix in the composite material and the molecular chains of the low-melting nylon 66 interpenetrate and entangle, thereby improving the interfacial bonding strength between the resin and the metal surface.

[0068] However, when the solubility of the coating is high, the interface layer formed between the composite material and the metal is thicker, and the thickness of the molecular chain of the resin matrix in the composite material and the molecular chain of the low-melting point nylon 66 is limited, which is lower than the thickness of the interface coating layer. Since the mechanical strength of the low-melting point nylon 66 resin is lower than that of the composite material, when subjected to a large load, the damage mainly occurs at the interface low-melting point nylon 66 resin, so the interface bonding strength is reduced. However, when the metal surface is coated with nylon 66 with a higher melting point (Tm = 260°C), due to the low mold temperature, the resin temperature of the composite material injected into the mold will drop quickly, which is not enough to melt the nylon 66 resin on the metal surface, thus resulting in a decrease in the interface bonding strength.

[0069] The above contents are merely preferred embodiments of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described, or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength, characterized in that: Includes steps: Step 1, cleaning the metal sample to remove the oil on the surface, and chemically etching the part connected to the injection-molded nylon resin to obtain a metal with porous and hydroxyl groups on the surface; Step 2, coating the metal surface treated in step 1 with a nylon solution, drying to remove the solvent, and then annealing to obtain a metal surface coated with nylon; Step 3, subjecting the metal with nylon coating on the surface in step 2 to injection molding nylon resin through ultrasonic assisted injection molding to obtain the metal and nylon heterogeneous connection material.

2. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 1, characterized in that: In step 1, the method of removing the surface oil stains includes one or more of inorganic alkali washing, organic solvent washing, aqueous detergent washing, and steam washing; The inorganic alkali washing specifically includes: washing the metal with 0.01-10 mol / L sodium hydroxide for 5-60 minutes.

3. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 1, characterized in that: The chemical etching process in step 1 includes the following steps: Step a, immersing the metal of the part connected to the injection-molded nylon resin after degreasing into a hydrochloric acid solution, taking it out, washing and drying it; Step b, immersing the acid-treated metal area in an aqueous ammonia solution, taking it out, washing it, and drying it.

4. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 3, characterized in that: The concentration of the hydrochloric acid solution is 0.01-10 mol / L, and the acid treatment time is 1-60 min; the concentration of the ammonia solution is 0.5-20 mol / L, and the ammonia treatment time is 1-60 min.

5. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 1, characterized in that: The melting point of the injection molding nylon resin in step 3 differs from the melting point of the nylon in the nylon solution in step 2 by 20 to 150° C. The mass concentration of nylon in the nylon solution is 0.01 to 20%, and the solvent is one or more of formic acid, trifluoroacetic acid, and phenol.

6. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 1, characterized in that: The nylon used in the nylon solution in step 2 includes one or more resins including nylon 6, nylon 66, nylon 1010, high temperature nylon 6T, high temperature nylon 9T, high temperature nylon 10T, high temperature nylon MXD6, and nylon copolymer; The metal includes one or more of aluminum, aluminum alloy, copper-aluminum alloy, magnesium-aluminum alloy, and magnesium-titanium alloy.

7. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 1, characterized in that: The injection molding nylon resin in step 3 includes one or more resins or fiber-reinforced resin composites selected from nylon 6, nylon 66, nylon 1010, high-temperature nylon 6T, high-temperature nylon 9T, high-temperature nylon 10T, high-temperature nylon MXD6, and nylon copolymers; and the fibers include one or more selected from glass fibers, carbon fibers, ceramic fibers, and aramid fibers.

8. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 1, characterized in that: In step 2, the drying temperature is 60-120° C., and the drying time is 0.2-2 h. In step 3, the ultrasonic power during the injection molding process is 100-1000 W, and the ultrasonic time is 3-20 s.

9. The method for preparing a metal and nylon heterogeneous connection material with strong interface bonding strength according to claim 1, characterized in that: The injection molding process is as follows: barrel temperature 250-380°C, mold temperature 60-200°C, holding pressure 40-160MPa, and cooling time 1-30s.

10. A metal and nylon heterogeneous connection material with strong interface bonding strength obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Metal-plastic composite and preparation method thereof

    CN117698038A

  • Metal surface treatment method based on nano injection molding and application

    CN118809931A

  • Metal-resin compound and preparation method thereof

    CN105729717A

  • Metal-resin composite

    JP2001047462A

  • Composite of aluminum alloy and resin and production method thereof

    JP2007182071A